Hepatitis B Virus Reactivation Potential Risk Factors in Hepatocellular Carcinoma via Transcatheter Arterial Chemoembolization: A Retrospective Research - Xiaoguang Wang; Xiaodan Yang; Fei Chen; Shaohan Wu; Zhengwei Song; Jianguo Fei (Canadian Journal of Gastroenterology and Hepatology)
Background. To explore the clinical characteristics of reactivation of hepatitis B virus (HBV) in hepatocellular carcinoma (HCC) after transcatheter arterial chemoembolization (TACE). The pathological correlation of prognosis and hepatitis B virus reactivation has been given detailed analyses in our research. Methods. A total of 108 related TACE-treated HCC clinical data from January 2008 to January 2016 was gleaned and involved in this retrospective analysis. To lucubrate the nuance of survival rates between HBV reactivated group and HBV nonreactivated group, clinical data of each patient was analyzed in detail and refined the retrospective studies. Results. HBV reactivation occurred in 42 patients with a proportion of 38.9%. The detected HBV DNA level ≥104 in patients showed a reactivation rate of 65.8% (25/38), which was significantly higher than the HBV DNA < 104 cases (24.3%, 17/70). Research data revealed a conspicuous lower cellular immunity (P<0.01) and better 2-year survival rate (P=0.03) in the HBV-reactivated group when compared to the nonreactivated group. Conclusion. Some of the patients with primary hepatocellular carcinoma possibly had HBV reactivation at post-TACE-therapy. And the predominant risk factors of HBV reactivation are positive HBV test and immunosuppression. Our study suggested that HBV reactivation at post-TACE-therapy is an independent predictor of poor prognosis and low survival rate as well as a crucial reason for poor prognosis and lower survival rate, which indirectly proved that it is urgent to necessitate the antiviral therapy and immune enhancer in improving the curative effect and prognosis of HCC patients.